ANALISIS PENGELOLAAN DANA DESA DALAM PEMBERDAYAAN MASYARAKAT DI KABUPATEN BATANGHARI (STUDI KASUS DESA SENGKATI BARU KECAMATAN MERSAM) - Putri, Syalila Suci; Nurjanah, Rahmah; Parmadi, Parmadi (Jambi Accounting Review (JAR), 2026)
The purpose of this study was to analyze the management of Village Funds in community empowerment in Sengkati Baru Village using qualitative and quantitative descriptive methods. The results showed that Village Fund Management in Sengkati Baru Village for the 2020–2024 period demonstrated highly effective performance, with a consistent 100% realization of the community empowerment budget. The main focus was allocated to the health sector, specifically accelerating stunting reduction, with a significant budget increase from IDR 59.2 million (2020) to IDR 267.3 million (2024). Although the efficiency ratio is categorized as very economical and community participation in village deliberations is high, the village faces challenges in the form of a halt in Village-Generated Revenue (PADes) since 2023 due to the cessation of PT DMP operations.